ASSESSMENT OF CHALLENGES AND VALUE-ADDED SERVICES OF COMMUNITY PHARMACIES FROM SATARA DISTRICT OF INDIA (International Journal of Food and Nutritional Sciences, 2022)
Community pharmacy is also known as retail pharmacy or pharmacy shop or chemist and druggist shop. These days management of retail pharmacy is challenging factor for community pharmacists. The study focuses on factors affecting as well as value added services provided by retail pharmacies of Satara district. The study also aims the impact of online pharmacy and organized pharmacy on community pharmacy practices. The study is both descriptive and explorative in nature. A survey method was used to capture data. A total of 178 community pharmacists participated in the study carried out for 8 months from 1st May 2021 to 31st December 2021. Sale value of the pharmacy was influenced by value added services as well as challenges faced by community pharmacists. Online pharmacy and organized pharmacy were major challenging factors for community pharmacies.